Designed to fail: Self-control and involvement in the criminal justice system - Delisi, Matt (American journal of criminal justice, 2001)
This study investigates self-control theory using official and selfreported criminal records of 500 adult offenders. Four items derived from rapsheets (aliases, date of birth, place of birth, and social security number) are used as indicators of the self-control construct. Negative binomial regression models indicate a significant inverse relationship between self-control and escape arrests, failure to appear violations, probation and parole violations, felony convictions, and prison sentences. Since system involvement entails discipline, tenacity, and responsibility, offenders with low self-control are more likely to experience a criminal justice system failure.